Some cases of "stone" in Peru - Manrique A., Juan (1957)
The "Stone" also called "ringworm Knobbly", "Stone of Colombia, Stone Nostras" etc., is a tropical parasitic disease of scalp hair, eyelashes, beard and mustache, which attacks the stalk of these, but not the root or the follicle. It is characterized by the formation of an irregular sheath, rounded, spindle shaped or lateral scales lumps, extremely hard and adherent, of white or black coloration, giving, to the touch, the feeling of small stones, and causing, in the hair, changes that ultimately make them gray, dry and friable. This disease has been observed in Europe and Japan. In South America was found, for the first time in Colombia, then in Brazil and then in Argentina, Paraguay and Venezuela.